Recent Developments in Azole Compounds as Antitubercular Agent - Das, Rina; Asthana, Gyati S.; Suri, Krishan A.; Mehta, Dinesh; Asthana, Abhay (Mini-Reviews in Organic Chemistry, 2019)
Tuberculosis (TB) is a global health disaster and is a wide-reaching hitch. The improper use of antibiotics in chemotherapy of TB patients led to the current problem of tuberculosis therapy which gives rise to Multi-Drug Resistant (MDR) strains. Nitrogen heterocycles including azole compounds are an important class of therapeutic agent with electron-rich property. Azole-based derivatives easily bind with the enzymes and receptors in organisms through noncovalent interactions, thereby possessing various applications in medicinal chemistry. Research on azoles derivatives have been expansively carried out and have become one of the extremely active area in recent years and the progress is quite rapid. A genuine attempt to review chemistry of azoles and to describe various azole-based compounds synthesized in the last two decades having promising antitubercular potential is described in the present article. It is hopeful that azole compounds may continue to serve as an important direction for the exploitation of azole-based antitubercular drugs with better curative effect, lower toxicity, less side effects, especially fewer resistances and so on.
Keywords: antitubercular drugs